Implikasi Kriminal Identitas Tadlis dalam Pernikahan: Tinjauan Hukum Islam Tentang Pembatalan Pernikahan dan Tanggung Jawab Pelaku - Tedy Subrata; Usman Musthafa; Agus Prihartono; Itang; Sayehu (Bulletin of Community Engagement, 2026)
This study examines the criminal implications of tadlis of identity (concealment or deception of identity) in marriage, focusing on its relationship to marriage annulment and the legal responsibility of the perpetrator under Islamic law and Indonesian positive law. The research discusses acts of concealing or falsifying identity, marital status, age, or other administrative data that form the basis for the validity of a marriage contract and its official registration. Using a normative legal research method with statutory, conceptual, and case approaches, this study analyzes primary legal materials, including the Indonesian Marriage Law, the Compilation of Islamic Law (KHI), the new Indonesian Criminal Code (Law of the Republic of Indonesia Number 1 of 2023), and the Population Administration Law, as well as secondary materials such as court decisions and Islamic legal literature on fraud (tadlis). The findings reveal that identity tadlis constitutes a form of fraud that undermines the essential elements of consent and honesty in the marriage contract (ijab qabul), thereby serving as a strong legal basis for marriage annulment under both Islamic law (as fasakh) and positive law (Article 27 paragraph (2) of the Indonesian Marriage Law and Article 72 paragraph (2) of the Compilation of Islamic Law). Furthermore, perpetrators may incur criminal liability when such acts fulfill the elements of document forgery, manipulation of population administration data, or concealment of lawful impediments to marriage, particularly under Articles 402–403 of the new Criminal Code. Consequently, the resolution of identity fraud cases in marriage should be approached through an integrated perspective encompassing Islamic law, family law, and criminal law, as marriage annulment and criminal sanctions address different yet complementary legal functions.